Are Beta Parameters Stable on the Warsaw Stock Exchange? - Dębski, Wiesław; Feder-Sempach, Ewa; Świderski, Bartosz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
Beta parameter is one of the commonly used measurements of individual stockor portfolio investment risk and plays a crucial role in modern portfolio theoryparticularly in management of financial investment portfolios. Many studieshave been done in this field, particularly on its properties such as stability in thecontext of the stock market cycle phases, measuring frequency of rate of return,length of sample period. However, the number of studies concerning beta parameterin the counties of Central and Eastern Europe that have undergone systemictransformation at the end of the previous century is much lower. Therefore wedecided to study the changes of behavior of the beta parameter in those countries.The main aim of this article is to examine the beta parameter stability over bulland bear market conditions on the Warsaw Stock Exchange. The paper presentsan analysis of betas stability for 134 stocks of the largest companies listed at theWSE during years 2005–2013.